Hypothalamus-Pituitary Dysfunction as an Independent Risk Factor for Postoperative Central Nervous System Infections in Patients With Sellar Region Tumors - Wen, Junxian; Yin, Rui; Chen, Yihao; Chang, Jianbo; Ma, Baitao; Zuo, Wei; Zhang, Xiao; Ma, Xiaojun; Feng, Ming; Wang, Renzhi; Ma, Wenbin; Wei, Junji (Frontiers in Endocrinology, 2021)
Objective: The purpose of this study was to verify that hypothalamus-pituitary dysfunction is one of the risk factors for postoperative central nervous system infections (PCNSIs). Method: We performed a retrospective analysis of all patients with sellar region lesions who underwent surgery between January 2016 and November 2019 at Peking Union Medical College Hospital. In total, 44 age‑ and sex-matched controls were enrolled. Univariate and multivariate analyses were performed to identify risk factors for PCNSIs. Result: We enrolled 88 patients, 44 of whom had PCNSIs. Surgical approach (TCS) (P<0.001), previous surgery on the same site (P=0.001), intraoperative cerebral spinal fluid (CSF) leakage (P<0.001), postoperative adrenal insufficiency (P=0.017), postoperative DI (P=0.004) and the maximum Na+ levels(<0.001) correlated significantly with PCNSIs. Multivariate analysis showed that Surgery approach（TCS）(OR: 77.588; 95%CI: 7.981-754.263; P<0.001), intraoperative CSF leakage (OR: 12.906; 95%CI: 3.499-47.602; P<0.001), postoperative DI (OR: 6.999; 95%CI:1.371-35.723; P=0.019) and postoperative adrenal insufficiency (OR: 6.115; 95%CI: 1.025-36.469; P=0.047) were independent influencing factors for PCNSIs. Conclusion: TCS, intraoperative CSF leakage, postoperative DI and postoperative adrenal insufficiency are risk factors for PCNSIs in patients with sellar region tumors. Conclusion: Intraoperative CSF leakage, postoperative DI and postoperative adrenal insufficiency are risk factors for PCNSIs in patients with sellar region tumors.